Power Through Autonomy: How Women Gain Voice in Household Decisions - Mehreen Mookerjee; Manini Ojha (Global Labor Organization (GLO), 2025)
We examine the effect of women's control over resources on their relative decision-making power within households, using an Instrumental Variable approach. We construct a composite Resource Empowerment Index that captures women's access to and control over economic and informational resources, including money, bank accounts, mobile phones, and knowledge of financial tools. To identify causal effects, we exploit variation in neighbouring women's media exposure as a source of exogenous influence on an individual woman's REI. We find robust positive effects of greater resource empowerment on women's relative say in household decisions, with evidence of diminishing marginal returns at higher levels of autonomy. We also find significant heterogeneity with large effects for older women, unemployed women, women in rural areas, those in larger households, those with less educated husbands and those with no children or more daughters.
Keywords: J12; J13; D13; 330; Resource empowerment; ownership; relative decision-making; media exposure; instrumental variable; India